2011
DOI: 10.1007/s11104-011-0951-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pasture root growth and transpiration efficiency following the incorporation of organic manures into a clay subsoil

Abstract: Background & aim This study tested the hypothesis that manure incorporation in the top of the B horizon of a texture-contrast duplex soil would increase root growth and water uptake by pasture grasses. Methods It involved soil columns consisting of a sandy loam topsoil over a dense clay. Four soil treatments included (i) a control profile, and modifications to the upper 10 cm of the clay subsoil involving (ii) a lower bulk density and (iii) the incorporation of poultry and (iv) dairy manure into this layer. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…Consistent with these findings, organic amendments generally exerted a clear improvement on the RLD and RWD of maize relative to CO in our experiment ( Figures 5-7), because both soil temperature and water, being substantially influenced by organic amendments, affected plant root growth [17]. By contrast, Espinosa et al [35] found that manure incorporation severely impaired the total root biomass of grasses when organic amendments were applied in clay subsoil to overcome nutrient deficiencies.…”
Section: Maize Root Responses To the Organic Amendmentssupporting
confidence: 90%
“…Consistent with these findings, organic amendments generally exerted a clear improvement on the RLD and RWD of maize relative to CO in our experiment ( Figures 5-7), because both soil temperature and water, being substantially influenced by organic amendments, affected plant root growth [17]. By contrast, Espinosa et al [35] found that manure incorporation severely impaired the total root biomass of grasses when organic amendments were applied in clay subsoil to overcome nutrient deficiencies.…”
Section: Maize Root Responses To the Organic Amendmentssupporting
confidence: 90%
“…The DMA also enhanced shoot and root biomass of pasture grass [33]. Others found that DMA increased the yields of rice [20], wheat and maize [23], Italian ryegrass and prairie grass [33]. The present study showed that DMA increased the biomass of ryegrass grown in the mudflat soil by increasing soil fertility while decreasing soil salinity.…”
Section: Discussionsupporting
confidence: 72%
“…Miron et al [32] also confirmed that the DMA increased yield of forage. The DMA also enhanced shoot and root biomass of pasture grass [33]. Others found that DMA increased the yields of rice [20], wheat and maize [23], Italian ryegrass and prairie grass [33].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, mudflat saline soil was enriched with alkaline N, available P, and other nutrients from DMA, which provided sufficient nutrients for ryegrass growth as the first green manure. Previous studies also found that DMA increased biomass of sorghum-sudangrass [23], pasture grass, and ryegrass [24] grown in croplands. Biomass of ryegrass, Sesbania, and ryegrass as green manures for three consecutive seasons, tilled into the mudflat saline soil, can be decomposed and converted into soil organic carbon, which subsequently improved the chemical properties of mudflat saline soil.…”
Section: Discussionmentioning
confidence: 70%